Pengaruh Penggunaan Lahan Terhadap Kualitas Air Hulu Cisanggarung, Kuningan, Jawa Barat - Althaaf, Naufal; Nasihin, Iing; Nurdin, Nurdin (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2025)
Water quality is an important indicator of ecosystem health and the well-being of communities that depend on water resources. In Indonesia, water quality is increasingly threatened by human activities, including the Cisanggarung River in Kuningan Regency. Problems include water quantity that is not sufficient for needs and declining water quality, especially for drinking water. Water quality is influenced by the surrounding environment and pollution due to changes in environmental factors. This research examines land use in the Cisanggarung river basin (DAS) through satellite image analysis and measurement of physical and chemical water parameters. Spatial analysis using satellite image interpretation and water quality analysis involves measuring Dissolved Oxygen (DO), pH, water temperature, turbidity, Total Dissolved Solid (TDS), Biochemical Oxygen Demand (BOD), and Chemical Oxygen Demand (COD) according to SNI standards. The research results show that land use in the upper reaches of Cisanggarung is classified into 3 land uses, namely forest land use with an area of 337.88 ha (46.65%), agricultural/plantation land 262.6 ha (33.35%) and land use for settlements with area 143.74 ha (19.85%). The use of forest land has an influence on lower TDS and TN values, while the use of agricultural/plantation and residential land influences the BOD and COD values. Water quality from upstream to downstream of the river has increased in physical and chemical parameters, showing the significant influence of land use type on river water quality.